Of Time Gals and Mega Men: Empirical Findings on Gender Differences in Digital Game Genre Preferences and the Accuracy of Respective Gender Stereotypes - Lange, Benjamin P.; Wühr, Peter; Schwarz, Sascha (Frontiers in Psychology, 2021)
We investigated the accuracy of gender stereotypes regarding digital game genre preferences. In Study 1, 484 female and male participants rated their preference for 17 game genres (gender differences). In Study 2, another sample of 226 participants rated the extent to which the same genres were presumably preferred by women or men (gender stereotypes). We then compared the results of both studies in order to determine the accuracy of the gender stereotypes. Study 1 revealed actual gender differences for most genres—mostly of moderate size. Study 2 revealed substantial gender stereotypes about genre preferences. When comparing the results from both studies, we found that gender stereotypes were accurate in direction for most genres. However, they were, to some degree, inaccurate in size: For most genres, gender stereotypes overestimated the actual gender difference with a moderate mean effect size.